Establishment of Gill-Derived Primary Cell Cultures from Largemouth Bass (Micropterus salmoides) as an Alternative Platform for Studying Host–Virus Interactions - Ziwen Wang; Li Nie; Chenjie Fei; Jiong Chen (Fishes)
A primary cell culture derived from the gill tissues of largemouth bass (Micropterus salmoides) was successfully established and characterized, providing a physiologically relevant model for virological research. Gill tissues were enzymatically dissociated, and their cells were cultured in M199 supplemented with 20% fetal bovine serum at 25 °C, yielding optimal growth. Viral replication within these primary cells was confirmed by transmission electron microscopy, and further qRT-PCR demonstrated the upregulation of antiviral genes (IFN1, Mx1, ISG15, and Viperin). These primary gill cells of spindle-like morphology exhibited significantly higher susceptibility to Micropterus salmoides rhabdovirus (MSRV) compared to established cell lines, as evidenced by higher viral titers, thus establishing their suitability for studying host–virus interactions. Furthermore, these cells were amenable to genetic manipulation, with the successful transfection of an mCherry reporter gene using commercially available reagents. These findings highlight the utility of the largemouth bass gill-derived primary cell culture as an alternative in vitro system for investigating MSRV pathogenesis and host immune responses, which serves as a stepping stone for improved antiviral strategies in largemouth bass aquaculture.